A Population-Based Study of Peyronie's Disease in Turkey: Prevalence and Related Comorbidities. Issue 4 (1st December 2020) - Kadioglu, Ates; Dincer, Murat; Salabas, Emre; Culha, Mehmet Gokhan; Akdere, Hakan; Cilesiz, Nusret Can
Abstract: Introduction: Peyronie's disease (PD) prevalence varies between 0.39% and 20% and studies on PD prevalence are limited. Aim: This study aims to determine the prevalence of PD in males aged ≥30 years in Turkey and to evaluate etiological factors associated with it. Methods: The study was conducted in 12 regions of Turkey according to the Eurostat Nomenclature of Territorial Units for Statistics 1 classification and included 1, 208 patients. Survey questionnaires including questions about demographic features and basic health status as well as about diagnosis and etiology of PD were put forth to the volunteers who agreed to participate in the study. Diagnosis of probable PD was established by evaluating the questionnaires. Patients with a diagnosis of congenital penile curvature were excluded from the group with PD. Chi-square test, Fisher's exact test, and Mann-Whitney U test were used. Main Outcome Measure: The primary outcome analyzed in this article was the prevalence rate of PD in Turkey and the associated comorbidities. Results: The prevalence of PD was determined as 5.3%. The rates of participants with PD were found to be the highest in the 50–59 years group (27%) and in the North-East Region (20%). Compared with participants without PD, participants with PD were older (median: 52 interquartile range [41–64] vs 45 [37–55]; P < .001) and the rates of smokers (73% vs 60.9%; P = .036) and those having diabetes mellitus (17.5% vs 9.2%; P = .045), hypertension (14.3% vs 6.9%; P = .041), and heart failure were higher (7.9% vs 2.5%; P = .027). Male with PD symptoms preferred their partners on top during sexual intercourse (15.2% vs 34.1%; P < .001). This is the first study to evaluate premature ejaculation prevalence and related comorbidities with face-to-face interviews. Conclusion: The prevalence of PD was 5.3% in Turkey. Besides advanced age, smoking, position of sexual intercourse, and presence of comorbidities especially diabetes mellitus, hypertension, and heart failure were the factors associated with PD prevalence.